Dynamics of Work Relationship Status in the Era of Industrial Revolution Disruption 4.0 - T., Triyon; Marcelawati, Yeni (UI Scholars Hub, 2021)
The development of technology and science has encouraged the birth of a fairly rapidly growing industry; the Internet-based industry, also known as Industry 4.0. The birth of Industry 4.0 resulted in disruption in the labor sector from the production side due to changes in the status of employment relations and job security. It increasingly emphasizes capitalism in the global economy. This article will question the dynamics of the disruption in the Industry 4.0 era on the labor sector, especially in the status of employment relations. The status of employment relations is very important to be studied because it is related to social security and wages earned and job security. The data in the article are obtained from the results of research reports, journals, books, documents, and from internet sources. The data were obtained using a literature study and exploratory analysis. Analysis results showed that Industry 4.0 caused a disruption in the status of working relations, from the status of a permanent employment relations based on contract and outsourcing, to the status of freelance and precariat (odd jobs) relations. The broader impacts on the normative rights of workers were in the form of unclear wage systems, lack of social security and lack of career sustainability of workers. Therefore, a policy direction is needed to protect and improve workers’ abilities in facing Industry 4.0. Thus, it is hoped that workers will have the skills and bargaining power vis-a-vis the industry